Fog-aided identity privacy protection scheme for sensing users in mobile crowd sensing - Hui LIU; Renwan BI; Jinbo XIONG; Mingfeng ZHAO; Biao JIN; Jie LIN (网络与信息安全学报)
In mobile crowd sensing(MCS),attackers can reconstruct the social circle among sensing users,who use the social association information among sensing users and the correlation between the sensing user’s identity and sensing data to further attack a social alliance.In order to tackle this issue,a fog-aided identity privacy protection scheme is proposed.Firstly,two fog nodes are introduced which located at the edge of the sensing terminal.The one is task allocation center (TC) for handling the reasonable allocation of sensing tasks,and the other is data center (DC) for calculating sensing data.Furthermore,differential privacy is employed for preventing attackers from acquiring the specific social association weight of sensing users.Finally,in order to prevent attackers from obtaining the sensing users' identity information and sensing data at the same time,sensing users use different blind identities to communicate with TC and DC.Security analysis indicates that the proposed scheme can ensure the security of identity privacy information of sensing users in the process of completing sensing tasks.Experimental results show that the proposed scheme can protect the social association information between sensing users,and has a low delay.